A statistical study to find out to what extent the guidance of the Prophet Mohammed were applied in marital life: Case Study “River Nile State- Republic of Sudan" - Abdalla, Abdalla Ahmed Alkhalifa (Journal of Humanities & Social Sciences, 2022)
The research problem is represented in the frequent divorce in recent times due to that husband from are away from Appling Sunna in marital life. The research aims to find out to what extent husbands apply Sunna، a sample of 207 and 207 wives taken from the Nile River State in Sunna. The importance of this study is that it reveals the percentage of application of the Sunna in marital life، which guides the preachers to determine their priorities. In addition، it is striking that statistics can play a great role in the field of advocacy. After analyzing the data، the research concluded that the rate of application among women is higher than that of men، and also found that the application of Sunna related to emotion is weak. The research concluded that Women apply more than men to the Prophet’s guidance in the marital relationship، and official dealing away from emotion، which is governed by customs، is prevalent in the marital relationship، and there is weakness in the application of the Sunnah related to emotion in general and the percentage of application of the Sunnah related to emotion is higher at young ages، while the Sunnah related to official matters are higher at older ages The level of application of the Prophet’s guidance in the marital relationship is higher among the urbanites than the rural ones، and among the educated from the illiterate، and among the couples who are not related to those who are related to them، and there is a wrong understanding among men about the guardianship of the man over the woman، which made them ignore many traditions. The research recommended the necessity of awareness of the guidance of the Prophet، may God bless him and grant him peace، in married life، as many spouses are ignorant that many of the things that they do or do not do are originally Sunnah. And focus on the countryside more than the urban as well as focusing on Calling for customs and traditions that contradict the Prophet’s Sunnah and trying to change society’s concept of it. It also recommended the application of this study to other regions with application to other Sunnah so that the roadmap of the call to preachers in order of priorities becomes clear، as well as conducting a similar study in which the questioner addresses the reason for not applying some of the Sunnah in his married life.